Pendidikan Keluarga Dalam Budaya Melayu: Telaah Dari Perspektif Al-Qur’an dan Hadits - Farhana Athirah; Nur'azimah; Marhamah Ulfa (Akademika: Jurnal Keagamaan dan Pendidikan, 2024)
The importance of family education is a sentence that always comes to mind every time we see various cases and problems that occur in this era. Starting from cases of divorce, murder, suicide, bullying, to juvenile delinquency. It is not uncommon for various cases of these problems to occur as a result of a lack of family education. Therefore, this research aims to find out how family education is in Malay culture, and whether family education in Malay culture is in accordance with the Koran and hadith which are the basis of Malay cultural customs. This research uses a library research method which uses reading references from both libraries and online media to obtain the required information data. The results of this research include the obligation of husbands to educate their wives and the obligations of parents to educate their children. Through proper understanding and implementation of the values ​​of the Qur'an and hadith, it is hoped that family education in Malay culture can become a strong foundation for building a harmonious family and preventing cases of detrimental problems in society.